VAN NIEKERK, Gerhardus Lourens Hartman Inventory of documents - VAN NIEKERK, Gerhardus Lourens Hartman (ARCA, 2018)
Private papers of G.L.H. van Niekerk, National Party MP Boksburg [1958-1965]; Senator [1965-1970].
COVERAGE 1925-1955; 10 Files; 0,11 Metres. AUDIO CASSETTES IN ARCA COLLECTION = 2
Keywords: VAN NIEKERK, Gerhardus Lourens Hartman; Inventories; Politicians; National Party